Experimental evidence for a magnetic sense in Neotropical migrating butterflies (Lepidoptera: Pieridae) (2006)
We tested whether migrating Aphrissa statira butterflies orient with a magnetic compass. We captured migrants flying over Lake Gatun, Panama, and exposed experimental butterflies to a strong magnetic field. These and unmanipulated control butterflies were released back over the lake. Experimental butterflies had a more dispersed pattern of orientation than control butterflies. The average direction adopted was northeast, 160° anticlockwise to the natural migratory direction. Unmanipulated control butterflies adopted two diametrically opposed orientations: one shifted 33° clockwise, and another 147° anticlockwise, to the migratory direction. Control and experimental butterflies differed in that some controls oriented towards the migratory direction. These differences in orientation support the hypothesis of a sense for magnetic orientation cues. Unmanipulated butterflies released over the lake when the sky was completely overcast were significantly oriented towards their direction before capture (187° and 203°, respectively), further supporting the magnetic compass hypothesis. In a third experiment, we obstructed sun compass cues and reversed the horizontal component of the local geomagnetic field to position magnetic north towards the geographical south pole within a flight arena into which we released individual butterflies. Experimental butterflies experiencing the reversed magnetic field oriented on average 180° opposite to their natural migratory direction. Control butterflies, for which the position of magnetic north was unaltered, were oriented both towards and 180° opposite to the natural migratory direction. This difference between orientations of control and experimental butterflies also supports the hypothesis of a sense for magnetic orientation cues.